Hvalfangsforhandlingene i historisk og prinsipielt perspektiv: økonomi, biologi, politikk - Midgaard, Knut (Forskningspolitiske spørsmål i norsk biologi : en seminarrapport = Policy issues in Norwegian biological research : report from a seminar, 1974)
I. Vi skal i det følgende beskjeftige oss med forhandlingene om regulering av den pelagiske hvalfangst i Antarktis med sikte på å belyse to emner: 1) betingelsene for at biologers premisser skal slå igjennom i en politisk prosess som gjelder utnyttelsen av levende ressurser, 2) rollekonflikter som kan oppstå for biologer som går inn i en slik prosess. Jeg vil først gi en historikk, og så gå nærmere inn på de to emnene.
https://hdl.handle.net/11250/2486546
Keywords: Den internasjonale hvalfangstkommisjonen; Norge; Sørishavet; hvalfangstkonvensjonen; hvalfangstkvoter; internasjonal politikk; pelagisk hvalfangst

The New Development in the Polar Regions - Sollie, Finn (Cooperation and Conflict, 1974)
Due to factors connected with modern technological developments and with the increasing global demand for new sources of raw materials, there is today a growing interest in the possibilities for economic exploitation of the polar regions. This makes for a new development in these regions; a development comprising and affecting such fields as science and technology as well as economy, transportation, military strategy and ecology. The present paper discusses this new development and its implications in an international perspective. Special attention is paid to the significance - in the physical/ geographical sense and otherwise - of the polar regions in the global context. A special section deals, on a general level, with 'the problem of the new territories', and the polar regions are discussed as new territories. Pointing out the risks and dangers inherent in the present and emerging developments, the author emphasizes the need for action, especially international cooperation, to meet and solve such problems. Cooperation may be facilitated through regular consultations between the states concerned, as is the case under the Antarctic Treaty. For the Arctic in particular, the author suggests a distinction between three basic zones (viz. the 'Central' the 'Intermediate' and the 'National' Arctic) as a possible point of departure for future discussion of measures of international cooperation.
Publisher: Sage Publications, Ltd.
Keywords: Antarktis; internasjonal politikk; polarområdene

The political experiment in Antarctica - Sollie, Finn (Bulletin of the Atomic Scientists, 1970)
General discussion of international cooperation in Antarctica. In special issue Antarctica since the IGY; international laboratory for science and diplomacy.
Publisher: Routledge In special issue Antarctica since the IGY; international laboratory for science and diplomacy. Reprinted in Lewis, Richard S. and Smith, Philip S., eds., Frozen future: a prophetic report from Antarctica, New York, 1973.
Keywords: Antarktis; Antarktistraktaten; internasjonal politikk; internasjonal rett; internasjonal samarbeid